Անդրանիկ Ծառուկեանի նամակները Նիկողոս Սարաֆեանին (1947-1958) - Շէնեան, Արթիւր (տպ. Atlas)
The collection presents fourteen letters from prominent Diaspora Armenian writer Antranig Dzarugian (1913-89) to French-Armenian poet Nigoghos Sarafian (1903-72), written between 1947 and 1958. The letters provide valuable insights into the literary landscape of the time, reflecting Dzarugian’s editorial approach and his unique perspectives on a range of literary phenomena. They also highlight his strong personal bond with Sarafian, marked by Dzarugian’s generous support for Sarafian’s work. The correspondence serves as a crucial resource for understanding the dynamics of Armenian literary circles in the mid-20th century Diaspora.
Keywords: Նամակագրութիւն